Letter (copy) : Spain - Citrine, Walter, 1887-1983
011-0039-001 WMC/EAB/AC/21 International STRICTLY CONFIDENTIAL 22nd September, 1937 Mr. W. Schevenels, International Federation of Trade Unions, 9, avenue d'Orsay, PARIS VIIe. Dear Comrade Schevenels, SPAIN. At a meeting of the National Council of Labour which took place today, the decision of the recent joint International Conference was considered, together with a report of the delegation to Geneva, where it had been suggested that the French Government were contemplating opening their Spanish frontier. During my conversations with Mr. Eden in Geneva, I mentioned this fact, and was informed that the French Government had not conveyed this intention to the British Government. Subsequently, however, I learned that it was the intention of M. Delbos, the French Foreign Minister, to have a conversation with Mr. Eden on this point on Monday, September 20. Whether this conversation took place, I am unable to say, but in view of the decision of our National Council of Labour to send a deputation to Mr. Eden for the purpose of urging upon the British Government the desirability of indicating its full support in the event of the French Government taking this step, I would like to be in a position to be able to say whether or not the French Government have approached the British Government. I shall be glad therefore If you will be good enough to find out through Jouhaux, or some other person, whether this intention has, in fact, been conveyed to Mr. Eden. I am endeavouring to arrange for the deputation to take place this week, but this may not be possible. In any case, will you try to get this information, and let me know, wither by telephone or express letter, by Friday morning. Yours sincerely, General Secretary. 292/946/11/39